2019
DOI: 10.7324/jabb.2019.70213
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diet and temperature on enzymes, hormones, and fecundity of the African Catfish Clarias gariepinus (Burchell 1822)

Abstract: The aim of this study was to check the effect of multiple temperatures and various protein diet formulas on liver enzymes, gonadotropins, and growth hormone (GH) using African catfish Clarias gariepinus. C. gariepinus was exposed to multiple temperatures (T 24°C , T 28°C , and T 32°C ) and various protein diet formulas: D 1 (fishmeal-based diet), D 2 (soymeal-based diet), and D 3 (pea-meal based diet). Tilapia commercial feed (D 4 ) was used as reference diet. A total of 720 individuals with an average weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…ALT and AST are secreted and expressed by the liver and are usually released into the blood in small amounts [16]. Previous studies on puffer fish Takifugu obscurus and Wuchang bream Megalobrama amblycephala Yih showed that the activities of ALT and AST were increased sharply after heat stress, and the liver was damaged [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALT and AST are secreted and expressed by the liver and are usually released into the blood in small amounts [16]. Previous studies on puffer fish Takifugu obscurus and Wuchang bream Megalobrama amblycephala Yih showed that the activities of ALT and AST were increased sharply after heat stress, and the liver was damaged [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are mainly found in the liver, and damage to the liver causes them to be released into the blood in large amounts [15]. Therefore, the levels of ALT and AST are important indicators to check whether liver function is normal [15][16][17].…”
Section: Introductionmentioning
confidence: 99%